China's trans-regional entrepreneurship: A panel data analysis of 31 provinces. Issue 3 (26th August 2014) - Song, Lin; Winkler, Christoph
Abstract : Purpose: – The purpose of this article is to analyze the supply (technology, education, labour, unemployment and real estate development) and demand (fiscal revenue and resident income) factors that influence regional entrepreneurial activity in China. Entrepreneurship develops at a rapid pace in China with significant differences among the country's regions. Design/methodology/approach: – Statistics of 31 Chinese provinces from 2005 to 2010 were collected, and an econometric model of the panel data was established. Findings: – Empirical results show that technology and employment positively impact on regional entrepreneurial activity. A subsequent analysis comparing data from 2005-2008 to 2009-2010 showed that different variables on regional entrepreneurship weaken during a period of financial crisis, with technology remaining as the only significant variable across all models. Finally, the study summarizes China's entrepreneurial activity as primarily supply-driven. Research limitations/implications: – This study is limited by the data sources and index design, which may not fully capture all influences on regional entrepreneurship to determine whether an inflection point or other interaction mechanisms exist. Practical implications: – The study demonstrates a differential emphasis on the impact of economic supply factors in a developing economy to positively affect entrepreneurial activities and sustained economic growth at the regional level. Conversely, it can be inferred that increased government spending during an economic crisis positively influences regional entrepreneurial activities. Originality/value: – The study contributes toward the development of a theoretical framework that emphasizes the relationship between entrepreneurial activities and its regional supply and demand factors. The overall model and findings highlight technology's importance on the development of innovation clusters that spur industrial agglomeration.